Interleukin-6 in peripheral blood and inflammatory sites in Behçet's disease - K. Hamzaoui; A. Hamzaoui; A. Kahan; M. Hamza; A. Chabbou; Kh. Ayed (Hindawi Limited, 1992)
Interleukin-6, a potent pro-inflammatory cytokine, might be involved in Behçet's disease (BD) pathological pathways. We investigated IL-6 levels in sera and synovial fluids collected from BD patients. The IL-6 production was also studied in vivo, by measuring its activity in culture supernatants of PBMC and alveolar macrophages, stimulated or not with LPS. The patients with BD were compared to RA patients and healthy controls. High IL-6 levels were observed in sera, synovial fluid and LPS stimulated PBMC supernatants, from active BD patients, similar to those of RA patients. Alveolar macrophages production of IL-6 was significantly elevated in two active BD patients with an interstitial pneumonia, when compared to controls. These elevated levels of IL-6 suggest its involvement in the inflammatory sites of BD, which may be related to the progression of the acute lesions, at least in the joints and in the lungs.